The Survival and Prognosis Characteristics of Primary Esophageal Small-Cell Carcinoma. (30th September 2022) - Li, Jie; Zhang, Xiangmei; Xu, Xinjian; Zhao, Qi; Yang, Qing; He, Ming; Chen, Xin; Zhao, Jidong
Abstract : Objective . To comprehensively explore the survival characteristics of primary esophageal small-cell carcinoma (PSCCE) and identify the main factors affecting the prognosis. Methods . The clinical and follow-up data of PSCCE patients admitted to the Fourth Hospital of Hebei Medical University from 2006 to 2010 were retrospectively analyzed. The primary endpoint was five-year survival. Survival curves were drawn using the Kaplan-Meier method, and log-rank test was used to compare the differences in survival rates among the groups. Cox regression models were used to analyze prognostic factors. Results . A total of 119 eligible patients were retrieved. Median survival was 27 months (3-100 months). Changes in overall survival (OS) in PSCCE patients were associated with TNM stage (P = 0.007 ), T stage (P = 0.049 ), and lymph node metastasis (P = 0.004 ). When TNM was in stage I-IIb, lymph node metastasis (P = 0.003 ) or combined adjuvant therapy (P = 0.004 ) was an independent factor affecting OS. Survival analysis showed that TNM staging had no predictive value for 5-year survival time or disease-free survival (DFS) of PSCCE (P > 0.05 ). Conclusion . TNM stage, T stage, and lymph node metastasis were related to the survival of patients. Negative lymph node metastasis and treatment are independent prognostic factors in PSCCE TNM stage I-IIb patients.